Mesophyll conductance response to short-term changes in pCO2 is related to leaf anatomy and biochemistry in diverse C4 grasses - Pathare, Varsha S (The New phytologist, 2022)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.